Beyond reductionism: Multidisciplinary insights approach for an effective climate change and sustainability policy - Andrzej Strzałkowski (Economic and Environmental Studies (E&ES), 2019)
Climate change and other sustainability problems represent unprecedented challenges to humanity today. Because of such challenges there is a need for fundamental social changes of current unsustainable society. There is essential advanced interdisciplinary scientific contribution for informing policy interventions. However, so far the state of development of this agenda is definitely insufficient. Scientific and policy discourse concerning climate change and sustainability is dominated by natural sciences, technical, and economic perspectives, while many crucial social sciences, especially sociology, anthropology, and ethnography are marginalized. Unfortunately, development of sustainability science and behavioural insights (behaviorally informed interventions, BIP) do not compensate this cognitive gap which could result in considerable ineffectiveness of current climate change and sustainability policy. From the observation that inconsiderate deepening of integration of various perspectives could lead to dramatic reduction in their explanatory power author moves to potential ways to diminish such threats and simultaneously successfully combining perspectives from different disciplines. Thereby, he proposes Multidisciplinary Insights Approach as a platform for practical collaboration between scientists from different disciplines and as a theoretical approach for developing more balanced and heterogeneous multidisciplinary agenda. The application of MIA was presented with the use of social practice theory, COM-B, and a couple other perspectives on the example of eating practice. This example showed that practice theory could be successfully used in indicating the general targets of interventions while the behavioral COM-B in detailed these interventions - all of these without excessive violations of both paradigms.
Keywords: Z13; D03; E03; Q58; P41; 330; Social practice theory; behavioural insights; COM-B; interdisciplinary; sustainability transitions